The Effect of Service Quality and Social Media Marketing on The Purchase Decision in Roemah Coffee - Firman Hidayat; Ratih Hurriyati; Maulana, Yono; Romlah (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
Business developments that are happening at this time make a lot of competition in doing business increasingly tight between companies, one of which is the café business. Intense competition among business people requires business people to provide the best for their customers in order to increase purchasing decisions for a company. This study aims to determine the effect of product quality and social media marketing on purchasing decisions at Roemah Kesambi Coffee. The sample in this study was 96 people using incidental sampling. The data analysis method used is multiple regression analysis. The results of the partial research (t test) show that the product quality variable has a significant effect on purchasing decisions.